Biaxial tensile failure of short carbon-fibre-reinforced PEEK composites. (26th May 2021) - Kang, Huaipu; Qi, Lin; Dang, Haoyuan; Jin, Kanghua; Thomson, Daniel; Cui, Hao; Li, Yulong
Abstract: The biaxial tensile failure of short carbon fibre reinforced polyether-ether-ketone (SCFR-PEEK) composites is characterized in this paper. An improved cruciform specimen was proposed to apply biaxial stresses, and five different stress ratios were employed in experiments. The stress distribution within the gauge section is not measurable across the varying stress ratios, therefore it is not trivial to obtain stress-strain data in the experiments. In this work, a combined experimental and numerical approach was proposed to deduce the true material behaviour during biaxial tensile tests. A numerical model with consideration of anisotropy and plasticity was proposed, it was further calibrated with uniaxial experiments and then validated with biaxial tests. Through this approach, the failure stress states at different stress ratios were successfully obtained. Compared with the numerical results based on constitutive relations, numerical results with linear elastic simplification overestimate the biaxial tensile strength, and are not suitable for material with an apparent nonlinear segment. The biaxial tensile failure envelope matches the Tsai-Hill criterion, and equal biaxial tensile results can be used for determining interaction coefficient F 12 in the Tsai-Wu criterion. This research approach offers an accurate and reliable solution for biaxial tensile testing of materials with consideration of anisotropic and nonlinear behaviour. Graphical abstract: Image 1 Highlights: This paper investigates the biaxial tensile behaviors of extruded SCFR-PEEK by adopting an improved cruciform specimen. A constitutive model with consideration of anisotropy and plasticity has been proposed and validated with biaxial tests. Good strain distributions inside the gauge section have been confirmed by both experiments and simulations. An approximation of stress states inside the gauge section has been made with support from the numerical model. The obtained failure envelope has been used to benchmark two well recognized failure criteria.